12.3k views
0 votes
Solve the system of equations
y=x-3
y=x^2-5x+6

User Toolbox
by
5.3k points

2 Answers

0 votes

Answer:

(3,0)

Explanation:

Solve the system of equations y=x-3 y=x^2-5x+6-example-1
User MJ Montes
by
6.0k points
1 vote

Answer:

x=3 (double root)

Explanation:

We are told that y = x - 3.

Substituting x - 3 for y in the second equation yields:

x - 3 = x² - 5x + 6.

We need to rewrite this in the standard form of a quadratic equation:

Subtracting (x - 3) from both sides results in:

0 = x² - 5x + 6 - x + 3.

Combining like terms gives us:

0 = x² - 6x + 9,

which factors into (x - 3)(x - 3) = 0. Thus, there are two real, equal roots: x = 3 and x = 3.

Subbing 3 for x in the first equation gives us 3 - 3 = 0 = y..

Thus, the solution of this system of equations is (3, 0).

User Crytrus
by
6.2k points